Studi Kekuatan Sambungan Plat Pada Spot Welding Ditinjau dari Kekuatan Tarik dan Geser - Nofriadi Handra (JURNAL MECHANICAL, 2013)
AbstractThis event will be based on research with the desires of the author about what exactly is the appropriate Spot Welding was simply and commonly used in the car industry for the manufacture of karoseri. The purpose of this research is to know the time of good press to perform welding on a particular plate of black and Galvanized plates with a thickness of 1.2 mm Methods of research conducted the first test of the composition, process of making test samples, conduct further testing of welding, pull and slide on each individual plate types, data processing, data analysis, make form conclusions, and making reports. After doing some research and obtained results that is, press time is good at 3.5 seconds on each plate with the current 26 Amper. From the above data can be drawn the conclusion that the press at the time of welding point is very influential to the value of the tensile strength and shearing strength. Because at the time of the electrode to the weld material emphasis will generate heat, thus forming clots, heat process that happens will affect the result of the welding connection. Keywords: Spot Welding, Tensile Strength, Shear Strength, Connection Plates